Contactless and continuous monitoring of respiratory rate in a hospital ward: a clinical validation study - Toften, Ståle; Kjellstadli, Jonas T.; Kværness, Jørn; Pedersen, Line; Laugsand, Lars E.; Thu, Ole K. F. (Frontiers in Physiology, 2024)
IntroductionContinuous monitoring of respiratory rate in hospital wards can provide early detection of clinical deterioration, thereby reducing mortality, reducing transfers to intensive care units, and reducing the hospital length of stay. Despite the advantages of continuous monitoring, manually counting every 1–12 h remains the standard of care in most hospital wards. The objective of this study was to validate continuous respiratory rate measurements from a radar-based contactless patient monitor [Vitalthings Guardian M10 (Vitalthings AS, Norway)] in a hospital ward.MethodsAn observational study (clinicaltrials.gov: NCT06083272) was conducted at the emergency ward of a university hospital. Adult patients were monitored during rest with Vitalthings Guardian M10 in both a stationary and mobile configuration simultaneously with a reference device [Nox T3s (Nox Medical, Alpharetta, GA, United States)]. The agreement was assessed using Bland-Altman 95% limits of agreement. The sensitivity and specificity of clinical alarms were evaluated using a Clarke Error grid modified for continuous monitoring of respiratory rate. Clinical aspects were further evaluated in terms of trend analysis and examination of gaps between valid measurements.Results32 patients were monitored for a median duration of 42 min [IQR (range) 35–46 (30–59 min)]. The bias was 0.1 and 0.0 breaths min−1 and the 95% limits of agreement ranged from −1.1 to 1.2 and −1.1 to 1.1 breaths min−1 for the stationary and mobile configuration, respectively. The concordances for trends were 96%. No clinical alarms were missed, and no false alarms or technical alarms were generated. No interval without a valid measurement was longer than 5 min.ConclusionVitalthings Guardian M10 measured respiratory rate accurately and continuously in resting patients in a hospital ward.